2022
DOI: 10.1093/ijpp/riac099
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in pharmacy education: a systematic quantitative literature review

Abstract: Objectives Gamification involves applying game attributes to non-game contexts and its educational use is increasing. It is essential to review the outcomes and the efficacy of gamification to identify evidence to support its use in pharmacy education. This article systematically and quantitatively reviews and evaluates the alignment of learning outcomes and the quality of peer-reviewed literature reporting gamification in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 89 publications
0
16
0
3
Order By: Relevance
“…While little gamification has been deployed in CCM education training, it has been used more extensively in other venues. Gamification is currently used across multiple disciplines to introduce new knowledge, reinforce existing knowledge, learn new techniques and their application, decision-making, and procedural mentoring and can be extended to patient education as well (23,24,(37)(38)(39)(40). Gamification modalities include escape rooms, simulation competitions, leaderboards, clinical team training exercises, and augmented reality/virtual reality (AR/VR)-based games.…”
Section: Current Gamification Usesmentioning
confidence: 99%
“…While little gamification has been deployed in CCM education training, it has been used more extensively in other venues. Gamification is currently used across multiple disciplines to introduce new knowledge, reinforce existing knowledge, learn new techniques and their application, decision-making, and procedural mentoring and can be extended to patient education as well (23,24,(37)(38)(39)(40). Gamification modalities include escape rooms, simulation competitions, leaderboards, clinical team training exercises, and augmented reality/virtual reality (AR/VR)-based games.…”
Section: Current Gamification Usesmentioning
confidence: 99%
“…Research on geriatric pharmacy mainly focused on two specific themes: (1) the role of pharmacists in geriatric such as in Petrovic et al (2016), Riordan et al (2016), Lee et al (2015), Marengoni et al (2015) (2) geriatric pharmacy education such as in Hope et al (2023), Woodall et al (2022), Odegard et al (2007). The review of literature revealed the scarcity of geriatric pharmacy research in the Middle East, and only two research studies were found; Awad et al (2020) and Awad and Hanna (2019) and both were conducted in Kuwait.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the last ten years (2012-2022), the number of research papers using the term game-based learning has dramatically increased from 381 to 6,765 results, according to a SCOPUS research. The use of games as a strategy for active learning has been applied in all areas of healthcare ( 1 ), including pharmacy, as recently reviewed ( 2 , 3 ) and specific disciplines, such as pharmacology ( 4 ). This phenomenon can be explained by the fact that the use of games or game elements improve student engagement and that learning is optimized by gaming mechanisms, such as immediate feedback, active participation, repeated practice, motivation, and teamwork ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of games as a strategy for active learning has been applied in all areas of healthcare ( 1 ), including pharmacy, as recently reviewed ( 2 , 3 ) and specific disciplines, such as pharmacology ( 4 ). This phenomenon can be explained by the fact that the use of games or game elements improve student engagement and that learning is optimized by gaming mechanisms, such as immediate feedback, active participation, repeated practice, motivation, and teamwork ( 2 , 3 ). Although game elements are widely recognized as important for enhancing student motivation and learning outcomes, the underlying mechanisms are not yet well-understood.…”
Section: Introductionmentioning
confidence: 99%